Balancing efficiency and competitiveness in outsourcing decisions. (14th May 2009) - Itkis, Dan; Daim, Tugrul; Basoglu, Nuri
In today's highly competitive market and rapidly changing economy, businesses must continually make choices if they are to survive, choices that set themselves apart from the pack. Consequently, some of the most important choices a company must make are strategic and are the responsibility of management. For this reason, taking into consideration the current business environment where the creation of value in the eyes of the customer and the shareholder is paramount, it is nearly impossible to survive without outsourcing some part of the business. In fact, manufacturing outsourcing is one area in particular, due to the competitive pressures which very few companies can afford to ignore. However, outsourcing is not a risk-free adventure. Two of the most substantial risks that companies face when outsourcing to a manufacturing contractor is creating a competitor and counterfeiting. Thus, the objectives of this research are to determine the risks that companies have encountered when outsourcing their manufacturing, specifically focusing on the current academic literature, case studies and empirical data, then propose a framework for evaluating and mitigating those risks.